Football players on Twitter. A platform for self-promotion - Meso Ayerdi, Koldobika (2021)
The emergence of social media has provided footballers a novel and highly effective means of reaching out to and interacting with followers. This new twist in the relationship between players and fans has sparked recent debate (Cleland, 2009) on players’ attempts to connect with sports audiences and publicize their brand images via Twitter (Hutchins, 2011). This research analyses aspects of the Twitter behaviour of the five football players who compete in the major European leagues with the greatest number of Twitter followers such as how these athletes relate to their fans, who they talk to and what they talk about via this medium in order to determine how these individuals use Twitter to build personal brands and forge deeper connections between themselves and the clubs they play for and fans. Content analysis was used to detect message dissemination patterns and identify the main protagonists of Twitter conversations examined. Semantic networks and hashtag use were also analysed to identify significant correlations between words. NodeXL, one of the most widely employed open code software programs in social network analysis was used for this part of the analysis (Hansen, Shneiderman & Smith, 2010). One of the main uses they make of Twitter is linked to self-promotion. In addition, the profiles of these football players often support solidarity initiatives and campaigns.